Primary Hodgkin's Lymphoma of bone in 7-year-old- an exceptional case report of youngest child in literature. (2021) - Siddiqui, Durr-e- Amna; Akbar, Hira Feroz; Sadiq, Hassan; Iftikhar, Namirah; Khan, Muhammad Rahil; Raza, Muhammad Rafie
Clinical practice points: Rarely, hodgkin lymphoma (HL) can present as primary bone lymphoma (PBL) that is restricted to a single bone with or without regional lymph node involvement. Primary osseous hodgkin lymphoma (POHL) can present with B symptoms like fever, night sweats and weight loss. On radiological imaging, POHL is often misdiagnosed as osteomyelitis, osteosarcoma or Ewing sarcoma. This makes biopsy important and crucial for correct diagnosis. Primary unifocal bone HL is characterized as Stage I and has a better prognosis than Stage VI disease according to Ann Arbor Classification. Abstract: Hodgkin lymphoma (HL) is mainly considered a nodal disease but extra nodal involvement can also be seen with variable frequency. Solitary bone involvement in HL known as Primary osseous hodgkin lymphoma (POHL) is very rare. It is defined as a lymphoma that is restricted to the bone without any simultaneous organ or lymph node involvement at the time of initial diagnosis. Primary Hodgkin lymphoma of the bone can be very challenging to diagnose because of its rarity especially in children and its variable presentation. Here we report the youngest case of POHL in a girl 7 years of age. She presented with the left leg pain and B-symptoms of fever and weight loss. Initial workup and imaging were suggestive of infection or a bone tumor. Bone biopsy of left hip joint after the multiple courses of antibiotics revealed Reed Sternberg cells in the mixed inflammatory background with CD30 and PAX-5 immunohistochemical positivity confirming classical hodgkin lymphoma, mixed cellularity type. CD99 and CD1a were negative excluding ewing sarcoma and langerhan cell Histiocytosis respectively. Absence of significant lymphadenopathy or visceromegaly on staging computerized tomography (CT) scan confirmed a very rare POHL. She received standard conventional chemotherapy with radiation. Our patient is in remission for five years after treatment.